Opisać świat „nieprzedstawiony” z perspektywy kogoś, kto sam do niego należy. - Beburishvili, Giorgi (Postscriptum Polonistyczne, 2020)
Interview with Bartosz Żurawiecki, Polish journalist, film critic, columnist, writer and playwright, on the situation of homosexuals in the modern world, on LGBT art, coming out and homophobic discourse.